A systematic review on the role of environmental toxicants in stem cells aging. (December 2015) - Hodjat, Mahshid; Rezvanfar, Mohammad Amin; Abdollahi, Mohammad
Abstract: Stem cells are an important target for environmental toxicants. As they are the main source for replenishing of organs in the body, any changes in their normal function could affect the regenerative potential of organs, leading to the appearance of age-related disease and acceleration of the aging process. Environmental toxicants could exert their adverse effect on stem cell function via multiple cellular and molecular mechanisms, resulting in changes in the stem cell differentiation fate and cell transformation, and reduced self-renewal capacity, as well as induction of stress-induced cellular senescence. The present review focuses on the effect of environmental toxicants on stem cell function associated with the aging process. We categorized environmental toxicants according to their preferred molecular mechanism of action on stem cells, including changes in genomic, epigenomic, and proteomic levels and enhancing oxidative stress. Pesticides, tobacco smoke, radiation and heavy metals are well-studied toxicants that cause stem cell dysfunction via induction of oxidative stress. Transgenerational epigenetic changes are the most important effects of a variety of toxicants on germ cells and embryos that are heritable and could affect health in the next several generations. A better understanding of the underlying mechanisms of toxicant-induced stem cell aging will help us to develop therapeutic intervention strategies against environmental aging. Meanwhile, more efforts are required to find the direct in vivo relationship between adverse effect of environmental toxicants and stem cell aging, leading to organismal aging. Graphical abstract: Highlights: Stem cells are important target for environmental toxicants. Environmental toxicants induce stem cell aging involved in age related disease. Environmental toxicants affect stem cells at genomic, proteomic and epigenomic levels.